An Examination of Leisure Participation, Family Assessment and Life Satisfaction in University Students. (13th May 2015) - Tercan, Evren
Abstract: Families are found to be having important role for providing leisure opportunities for their members and also recreation activities are expected to contribute to family cohesion. Therefore, the aim of this study is to examine the relationship between leisure participation with family, family assessment and life satisfaction in university students of Akdeniz University. Sample of the study consisted of 985 students taking elective physical education courses (mean age = 21.67 ± 2.18). A questionnaire consisting of demographic questions, questions concerning leisure participation, family assessment scale and life satisfaction scales were utilized for data collection. Besides descriptive statistics, correlation, MANOVA, student t-tests were applied. According to the results, some subscales of family assessment had significant relations with life satisfaction (p < 0.05). Life satisfaction was higher in students who participated in recreational activities longer and more frequently than the other students (p < 0.001). As family is the basic unit of the society, students get their habits of leisure participation in family environment. Thus it is important to gain an understanding of family leisure and its contributions to the student's life.